Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

prove that cosecA(1+cosA)(cosecA-cotA)=1

prove that cosecA(1+cosA)(cosecA-cotA)=1

Grade:10

4 Answers

Varun Acharya
39 Points
7 years ago
Cosec A(1+cosA)(cosecA-cotA)=(cosecA+cosecAcotA)(cosecA-cotA) = (cosecA+cotA)(cosecA-cotA)= cosec^2A-cot^2A
venkat
39 Points
7 years ago
if we write the eqn in terms of sin and cos we get (1-cosA)*(1+cosA)/square(sinA) =>(1-square(cosA))/square(sinA) =>1
Varun Acharya
39 Points
7 years ago
Plz reply bru..... did u understnd the solution???
FAYAS TH
11 Points
3 years ago

(CosecA+CosecACosA)*(CosecA-(CosA/SinA))

 

(1/SinA)+(CosA/SinA)(1/SinA-(CosA/SinA))

 

(1+CosA/SinA)(1-CosA/SinA)

 

1-Cos^2A/Sin^2A

 

Sin^2A/Sin^2A

 

 ==1

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free